Representasi Pelecehan Seksual Terhadap Laki – Laki Dalam Film Dear David - Kandi, Nilam Tiara; Pradana, Hengki Hendra (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
This study aims to determine the representation of sexual harassment against men in the film Dear David which has a lot of teenage problems in it to find out the researchers used descriptive qualitative research methods with a semiotic analysis approach John Fiske model with three-level social codes, namely the level of reality, level of representation, level of ideology. Data collection by watching and observing several scenes to understand the content of the film, documentation and cutting several scenes of film images that represent representations of sexual harassment of men through literature studies, namely, collecting previous reference journals, websites, the internet, theses, and books related to this research. The results of this study indicate that the representation of sexual harassment against men is seen in the film Dear David with a general form of verbal and nonverbal and sexual fantasies as a trigger for sexual harassment, about sexual harassment against men who become a normal thing and masculinity in men with normal can be a material for sexual harassment as a joke that leads to coercive nonverbal harassment. This representation is intended to be informative regarding sexual harassment against men that is still considered normal and the patriarchal influence of society on men who still think that men cannot be victims of sexual harassment.